Fuzzy controlled evaporative battery thermal management system for EV/HEV - Rahman, Mohammed Ataur; ., NurFarahana; Hawlader, Mohammad Nurul Alam (2014)
Battery pack needs to generate a high output within a very short time to meet the power demand of the car at the time of momentary peak load. These peak load periods generate powerful electrical currents, causing significant warming of the Li-ion cells due to internal resistance causes internal cells damage. LiFePO4 batteries, however, can be used efficiently only within a desired operating temperature in the range 20ºC - 40ºC. The battery operating temperature of 40ºC and above, the battery life span is reduced. The rationale of this study is to develop an intelligent controlled evaporative battery cooling thermal management system (EC-BThMS) to control the battery temperature in the range of 20ºC - 40ºC in order to increase the battery life span and to improve the battery performance. The proposed thermal management system has been developed by developing the evaporative system with estimating the total cooling loads and thermal behavior of the cells of battery. The developed thermal management system is able to maintain the battery temperature in the range of 20ºC - 40ºC during discharging and charging process. The experiment on EC-BThMS was conducted both in IIUM and Sepang F1 international circuit. The experimental result of prototype EC-BThMS in SepangF1 has been conducted and compared with air-cooling battery thermal management system. It is found that the PROTON saga car with EC-BThMS can save 17.69% more energy than with AC-BThM 1 and 23% than with AC-BThMS 2. The correlations between the measured and predicted values of temperature profiles of the battery during operation have been found to be 97.3%. This is indicates that the predicted data over the measured data have a closed agreement and thus, substantially verified the mathematical model.